Governança regional do sus em Goiás: análise situacional para implantação do COAP - Paula, Dante Garcia de (2014)
Governance in the SUS is recognized as the ability to intervene in the system by different actors, instruments and procedures for shared regional management. Your institution through the inter manager instances of SUS is crucial to regional integrated planning process and achievement of Organizational Contract Public Health Action (COAP).The objective in this study is to analyze the conditions of regional governance in the SUS Goiás as guidance in the preparation of COAP. We used an intervention within the State Department of Health of Goiás (SES / GO). It was considered two groups of regional representation of SUS management, municipal managers and managers / regional supervisors, the 17 Health Regions, organized into 05 geographical regions health. The data were derived from 17 arrays called “consenso regional para implantação do COAP”, these consist of six-axis and 22 standart-questions, produce of management workshops and regional governance held at the V Meeting of Health of the State in 2013. It was also considered national and state standards and resolutions agreed by SUS. The data of the workshops are in public domain and are recorded in the annals of the V Meeting. The analysis considered as a representation of the colors of the consensus of the managers responses as follows: red, yellow and green seeing unfavorable, partially favorable and favorable, respectively. It was adopted the orange (red and yellow sum of responses). It was consolidated in 17 arrays in Microsoft Excell system into 05 geographical regions and converted to numbers in percentage charts. The results show: the weaker axes in regional governance is the Map of Health / General Development and Social Participation with 62.35 and 56.86%, respectively, of unfavorable reply. The ignorance of regional design, as well as the lack of services in some geographical regions show up 66.67% of unfavorable answers. It was prevailed low knowledge of programming and low use of health care attention, reaching up to 75.0% of non-favorable responses in some geographical regions. The integrated regional planning is disjointed and there is no good integration between the basic instruments to the guidelines, the health map, the targets and the indicators. The attention network appears as lack in some geographical regions and regulatory flows are not recognized by all.There is low knowledge about the RENASES AND RENAME and a total ignorance of the rules and flows to preparation of COAP (100.0%). It presents a proposal for intervention agenda with strategies to cope with weaknesses and schedule steps. The study indicates significant persistence of weaknesses in the regional governance of SUS in Goiás, however, it suggests strategies for the system to be deployed in COAP 17 Health Regions.